1960
DOI: 10.1083/jcb.8.1.61
|View full text |Cite
|
Sign up to set email alerts
|

Histochemical Demonstration of Dehydrogenase Activity in the Cells of Normal Human Blood and Bone Marrow

Abstract: Endogenous and succinic dehydrogenase activity was demonstrated in the living cells of normal human blood and bone marrow using a buffered nitro BT-succinate incubating solution. With this technique dchydrogenase activity was localized primarily in the granular leukocytes and the sites of cnzymatic activity appcared to be non-mitochondrial. The addition of a non-ionic surface active agent to thc incubating solution resulted in marked differences in the cellular and intracellular localization of dehydrogenase a… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
1
1

Citation Types

2
14
0
1

Year Published

1963
1963
1980
1980

Publication Types

Select...
4
2

Relationship

0
6

Authors

Journals

citations
Cited by 19 publications
(17 citation statements)
references
References 13 publications
2
14
0
1
Order By: Relevance
“…My finding that the specific granules are positive and resistant to amylase in Trichosurus parallels ACKERMAN's (1963) results with rabbit and guinea pig, and those of FEY (1966b) for some lower vertebrates.…”
Section: Pas Stainingsupporting
confidence: 53%
See 4 more Smart Citations
“…My finding that the specific granules are positive and resistant to amylase in Trichosurus parallels ACKERMAN's (1963) results with rabbit and guinea pig, and those of FEY (1966b) for some lower vertebrates.…”
Section: Pas Stainingsupporting
confidence: 53%
“…By biochemical analysis, however, it has been found that only a small part of the PAS-positive content of leukocytes is glycogen (OLSSON and DAHLQVIST, 1967). It seems generally accepted that the glycogen of neutrophils occupies an intergranular position, though ACKERMAN (1964) says that much of it may be associated with the specific granules. Working with fractionated cells, VERCAUTEREN (1965) concluded that most was associated with the smooth endoplasmic reticulum though the specific granules may contain some.…”
Section: Pas Stainingmentioning
confidence: 99%
See 3 more Smart Citations